Relationship between Students’ Learning Interests with their Language Learning Achievement - Agus Boriri; Yuliani Ishak (Jurnal Langua, 2020)
This research was conducted because of problems regarding learning interest and Indonesian learning achievement. This study aims to determine the relationship between learning interest and student learning achievement in the 2015 Indonesian Language and Literature education study program STKIP Kie Raha Ternate. This research was conducted at the Indonesian Language Study Program STKIP Kie Raha Ternate. The implementation time is 3 months. The population of this study were all 2015 Indonesian language and literature students and the sample used in this study was 35 students. The instrument used to obtain data in this study was a questionnaire and documentation in the form of a student achievement index (IP). The data obtained were analyzed using correlation test. After analyzing using the correlation test it turns out that there is a significant relationship between learning interest with the learning achievement of students of the Indonesian Language and Literature education study program year of 2015 STKIP Kie Raha Ternate and the magnitude of the relationship of learning interest with the learning achievement of students of the Indonesian Language and Literature education study program year 2015 STKIP Kie Raha Ternate is (0.021) 2 or 4.41%.